PENERAPAN NILAI PANCASILA MELALUI PEMBIASAAN SHOLAT BERJAMA’AH PADA ANAK USIA DINI - Yani Nuraeni; Elan Elan; Aprily Masum Nuraly (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2022)
Vulnerable early childhood age from in the womb to 6 years. Character education is applied to the child's golden age. Pancasila is the national guideline. The contents of Pancasila values are reflected in the congregational prayer movement. The first precept has the same meaning as divinity, with the prayer movement pointing the index finger indicating the one and only God, the second precept is illustrated in the placement of the front row when praying in congregation, namely the existence of equal rights. The third precept is depicted in the unification of Muslims in one place to strengthen brotherhood, the fourth precept is depicted in the congregational prayer movement led by one command, the fifth precept is illustrated in the prostration movement which lowers the head under the feet of the person in front of him, everyone before Allah. S.W.T is the same. This research uses literature study.